Dynamic Structure and Subsurface Oxygen Formation of a Working Copper Catalyst under Methanol Steam Reforming Conditions: An in Situ Time-Resolved Spectroscopic Study. ACS Catalysis - Daniel Ruano (2019)
The dynamic behavior of a CuO/ZnO/Ga2O3 catalyst under methanol steam reforming (MSR) reaction conditions promoted by a high dispersion of the copper nanoparticles and defect sites of a nonstoichiometric ZnGa2O4 spinel phase has been observed, where structural changes taking place in the initial state of the reaction determine the final state of the catalyst in stationary reaction conditions. Mass spectrometry (MS) studies under transient conditions coupled to X-ray photoelectron spectroscopy (XPS) have shown copper oxidation to Cu+ in the initial state of the reaction (TOS = 4 min), followed by a fast reduction of the outer shell to Cu-0, while keeping dissolved oxygen species in the inner layers of the nanoparticle. The presence of this subsurface oxygen impairs a positive charge to the uppermost surface copper species, that is, Cu delta+, which undoubtedly plays an important role on the MSR catalytic activity. The detection of these features, unperceived by conventional spectroscopic and catalytic studies, has only been possible by combining synchrotron NAP-XPS studies with transient studies performed in a low volume catalytic reactor connected to MS and linked with Raman and laboratory scale XPS studies.